Penegakan Hukum Aksi Premanisme Berbasis Program 3 Quick Wins Polri Oleh Kepolisian Daerah Daerah Istimewa Yogyakarta - Nidia Ratih (Universitas Janabadra, 2019)
Program quick wins the national police is the police force of the Republic of Indonesias priority program which is a program to 11 of the Program Professional, Modern and reliable. The Promoter of the program itself is a translation of policy directions and strategies in the strategic plan Police Stage III in 2015 2019 i.e. Strive For Excelence that is aligned with the vision and mission of the national police. Increasing numbers of criminality resulting from the action of thuggery that is troubling the community, become the basis of preparation of the program 3 quick wins the national police which is national action Cleansing thugs and Thuggery.Types of juridical research based empirical social. Descriptive research analytical specifications. The source of primary data from interviews of officials and investigators on site research, namely the Directorate General regional police Criminal Reserse Daerah Istimewa Yogyakarta. A secondary data source from the study of librarianship. The technique of data collection by means of field research, librarianship, and interviews. Methods of data analysis using qualitative, descriptive methods. Research produces conclusions: a the measures which have been carried out by the Police in dealing with actions that occur in the area of building regional police special region of Yogyakarta-based program with 3 quick wins the national police in this Directorate General with Criminal do: meeting coordination, implementation, and analysis of mapping and evaluation b Law enforcement and results obtained Yogyakarta regional police in dealing with action-based programs thuggery 3 quick wins the national police from the author's research results known to the thugs who haven't done the deed a criminal then done on logging and construction. As for the action elements that meet the criminal thuggery then conducted the investigation to legal certainty and meet the sense of Justice. And program implementation 3 quick wins this Police have obtained the results of the positive and negative impact either for officers as well as a sense of Justice in society.Keywords :program 3 quick wins police, thuggery, law enforcement